High thermal conductive silicone rubber composites constructed by strawberry-structured Al2O3-PCPA-Ag hybrids. (March 2021) - Yang, Dan; Wei, Qungui; Li, Bingyao; Yu, Liyuan; Ni, Yufeng; Zhang, Liqun
Graphical abstract: Abstract: Silicone rubber (SR) is commonly used as thermal conductive material due to its high thermal stability, good insulation, and excellent flexibility. However, its low thermal conductivity (λ) limits its wide applications. Here, high thermal conductive SR composites were prepared by incorporating strawberry-structured alumina-poly(catechol-polyamine)-silver (denoted as Al2 O3 -PCPA-Ag) thermal conductive hybrids. The strawberry-structured Al2 O3 -PCPA-Ag hybrids were synthesized by modification of Al2 O3 with poly(catechol-polyamine) (PCPA) followed by electroless plating of silver (Ag). The PCPA layer decreased the interfacial thermal resistance and Ag nanoparticles benefited the phonon transmission of SR composites. The as-prepared 30 vol% Al2 O3 -PCPA-Ag/SR composite showed a maximum thermal conductivity of 0.4367 W/mK, which was 3.3-fold higher than that of the SR matrix (0.1320 W/mK). Due to the Coulomb blockage effect of quantum-size Ag nanoparticles, the maximum AC conductivity of Al2 O3 -PCPA-Ag/SR composites at 100 Hz was 2.14E-12 S/cm. The proposed method provides a new strategy for preparation of high thermal conductive polymeric composites.